Alignment, orientation, and Coulomb explosion of difluoroiodobenzene studied with the pixel imaging mass spectrometry (PImMS) camera - Amini, Kasra; Boll, Rebecca; Lauer, Alexandra; Burt, Michael; Lee, Jason W. L.; Christensen, Lauge; Brauβe, Felix; Mullins, Terence; Savelyev, Evgeny; Ablikim, Utuq; Berrah, Nora; Bomme, Cédric; et al. (My University, 2017)
Laser-induced adiabatic alignment and mixed-field orientation of 2,6-difluoroiodobenzene (C6H3F2I) molecules are probed by Coulomb explosion imaging following either near-infrared strong-field ionization or extreme-ultraviolet multi-photon inner-shell ionization using free-electron laser pulses. The resulting photoelectrons and fragment ions are captured by a double-sided velocity map imaging spectrometer and projected onto two position-sensitive detectors. The ion side of the spectrometer is equipped with a pixel imaging mass spectrometry camera, a time-stamping pixelated detector that can record the hit positions and arrival times of up to four ions per pixel per acquisition cycle. Thus, the time-of-flight trace and ion momentum distributions for all fragments can be recorded simultaneously. We show that we can obtain a high degree of one-and three-dimensional alignment and mixed-field orientation and compare the Coulomb explosion process induced at both wavelengths.